Study and analysis of the coagulation factors and their natural inhibitors levels in apheresis derived platelet concentrate units over a five-day storage period - Pawar, Amit A.; Biswas, Amit K.; Dubey, Rounak; Bhowmik, Sujay (International Journal of Research in Medical Sciences, 2020)
Background: The possibility of utilizing clotting factors in the plasma phase of apheresis platelet concentrates, as a supplement to the standard FFP transfusion for clotting factor replacement needs to be explored. In this study, it was proposed to assess the effect of storage on clotting factors and inhibitors in stored apheresis platelet concentrates. This would give an insight into the hemostatic potential of the plasma phase of the apheresis platelet concentrates. Methods: This study was conducted on a sample size of 45 apheresis platelet concentrate units harvested on Amicus cell separator. Basic coagulation workup along with various coagulation factors and their natural inhibitors were studied in the apheresis platelet concentrates on day ‘0’ and day ‘5’ of the collection. Results: Prothrombin time and activated partial thromboplastin time of the apheresis platelet concentrates was increased on day ‘5’ of the collection but were within the normal range. Fibrinogen, Factor XII, and VWF: Ag showed an increase on day ‘5’ of collection. Protein C, protein S activity, and antithrombin decreased on day ‘5’ of collection. Also, Factors II, VII, IX, X, XI decreased on day ‘5’. The highest fall in activity was seen in the case of Factors V and VIII. Despite the fall, all the clotting factors were maintained within their normal range. Conclusions: Although the activity of most of the coagulation factors showed a decrease, it was maintained within their normal range and efficacy. Therefore, a reasonable hemostatic potential of the clotting factors is expected to be maintained in apheresis platelet concentrates after a storage period of five days at room temperature.